Sosialisasi Peraturan Desa (Perdes) Mario, Kecamatan Tanasitolo, Kabupaten Wajo - Andi Bau Mallarangeng; Muharawati; Nurhikmah; Ratih; Yuliani; Zulkifli; Andi Zulfikar; Miftahul Khair (Compile Journal of Society Service, 2025)
Dissemination of village regulations is a crucial step in ensuring that the community understands and complies with regulations established by the village government. According to Law Number 6 of 2014 concerning Villages, each village has the authority to regulate and manage government affairs and the interests of the local community. Therefore, effective dissemination can increase community participation in village development and create transparency and accountability in the management of village resources (KDPDTT, 2020). This community service research was conducted to disseminate regulations in Mario Village, Tanasitolo District, Wajo Regency using a lecture method (extension) to increase understanding regarding the importance of knowing and complying with village regulations. Through collaboration between KKN students from the Lamaddukelleng Institute of Science and Economics, the LEM Demokrasi (NGO), the village government, the BPD, and the community, this dissemination succeeded in increasing understanding regarding the importance of knowing and complying with village regulations.